Dietary antioxidants and obesity: a new perspective on the role of composite dietary antioxidant index in reducing obesity risk using a dual-criteria definition - Chen, Yi-Qian; Wang, Chen; Zhang, Yi-Jie; Zhang, Yue-Yang (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the association between the Composite Dietary Antioxidant Index (CDAI) and obesity defined by both BMI and waist circumference (WC).MethodsThis was a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) 2009–2018. Multivariable logistic regression models and restricted cubic splines were used to assess the relationship between CDAI and obesity, defined as BMI ≥ 30 kg/m2 combined with WC ≥ 88 cm (women) or ≥102 cm (men). Models were adjusted for sociodemographic, lifestyle, and comorbidity factors. A stratified analysis and sensitivity analysis were also conducted.ResultsAmong 17,067 participants, CDAI was inversely associated with obesity (OR: 0.97, 95% CI: 0.95–0.99). Participants in the highest CDAI quartile had a 23% lower obesity risk compared to the lowest quartile (OR: 0.77, 95% CI: 0.62–0.95). Subgroup and sensitivity analyses yielded consistent results.ConclusionCDAI is inversely associated with obesity defined by dual criteria, suggesting that dietary antioxidants may play a protective role in obesity prevention. By using a more comprehensive definition of obesity, our study provides insights that are more directly applicable to clinical practice and public health strategies aimed at reducing obesity-related morbidity and mortality.